Mg-Doped Carbonated Hydroxyapatite and Tricalcium Phosphate Anodized Coatings on Titanium Implant Alloys - Amisha Parekh; Maggie Moore; Amol V. Janorkar; Michael D. Roach (Applied Sciences)
The rising demand for dental and orthopedic implants and their frequent aseptic loosening failure mode necessitate the drive to continue modifying implant surfaces to improve osseointegration outcomes. Plasma-sprayed hydroxyapatite coatings are widely used but are prone to delamination. This study involves a single-step anodization process utilizing a novel electrolyte to produce Mg-doped carbonated hydroxyapatite and tricalcium phosphate-containing coatings on four titanium alloy surfaces. XRD confirmed hydroxyapatite and tricalcium phosphate formation, with FTIR examination revealing carbonate substitutions indicative of bone-like apatite formation in each oxide. SEM analyses revealed micro- and nano-scaled surface features on each oxide. SEM and EDS analyses of the oxide coating cross-sections showed each group to be bi-layered with an inner titanium dioxide-rich layer and an outer hydroxyapatite/tricalcium phosphate-rich layer. The oxide layer adhesion quality was shown to be good on CPTi, TAV, and TiMo α + β implant alloy surfaces. Unfortunately, the anodization process also resulted in an undesirable and embrittling omega phase at the substrate–oxide interface due to the migration of molybdenum into the inner oxide. Nonetheless, the anodized coatings on the CPTi and TAV alloy substrates, which are the most widely used titanium alloys for implant applications, show much potential for improving future patient outcomes.